Investigation microstructure and mechanical characteristics of sugar palm fibre ash reinforced LM26 Al-matrix composites - Isah, Aliyu; Salit, Mohd Sapuan; Zainudin, Edi Syams; Mohamed Yusoff, Mohd Zuhri; Yahaya, Ridwan (King Mongkut’s University of Technology North Bangkok, 2023)
Aluminium alloy of grade LM26 was used as a matrix and sugar palm fiber ash (SPFA) as reinforcement to investigate its microstructural and mechanical characteristics. Stir casting, a cost-effective method of casting was utilized to fabricate the composites, by altering SPFA from 0 to 10 wt% in 2 wt% increments in an LM26 Al-alloy matrix. The microstructural analysis and phase identification were identified with Scanning Electron Microscopy (SEM) attached to Energy Dispersive Spectroscopy (EDS) and X-ray Diffraction (XRD), respectively. The composites were tested for density, hardness, tensile strength, compression strength, and impact energy according to ASTM. Microstructural images revealed a homogeneous distribution of SPFA in the LM26 Al-alloy matrix. The phases identified in the composites were α-Al, hard SiO2, Mg2Si, and Al5FeSi. The addition of SPFA decreased the composite density and impact energy by 3.85% and 46.68%, respectively. The compression strength and tensile strength of the composites increased by 23.73% and 27.83%, respectively, at an 8 wt% addition of SPFA. However, further addition of up to 10 wt% SPFA showed a decreasing trend in compression and tensile strength. The hardness of the composites increased by 60.80% after a 10 wt% addition of SPFA. These findings showed that synthesized LM26 Al-SPFA composites could be used in the automotive industries for the fabrication of pistons, connecting rods, brake shoes, and other components due to their excellent mechanical characteristics.